First Report on the Reproductive Biology of Saurida tumbil in Jizan Waters, Saudi Arabia Based on Histological Analysis : Reproductive Biology of Saurida tumbil in Jizan Waters - Hartono, Sugeng; Santanumurti, Muhammad Browijoyo; Puspito, Gondo; Salsabila, Sahda; Abualreesh, Muyassar Hamid (Journal of Aquaculture and Fish Health, 2025)
A scientific study on Saurida tumbil is essential, particularly concerning fishing activities. The current study aimed to investigate the reproductive biology of Saurida tumbil through monthly sampling. Fish were dissected to determine sex and gonadal maturity stages, with gonads furthermore preserved in a 10% formalin solution. Reproductive parameters, including sex ratio, gonad maturity, length at first sexual maturity, gonadosomatic index (GSI), and fecundity, were analysed, followed by length at first capture analysis. Histological techniques were applied to assess gonadal maturity at a microscopic level. The peak reproductive period of Saurida tumbil in Jizan waters was identified between February and April (winter–spring), with the highest GSI values recorded for females (3.6) and males (0.96). Reproductive activity declined between October and December (autumn–winter). The estimated length at first sexual maturity was 23.49 cm for females and 23.94 cm for males. Both values were lower compared to length at first capture (22.75 cm). Absolute fecundity averaged 42528 eggs, ranging from 4485 to 225549 eggs. Identifying optimal fishing areas and seasons simultaneously in Jizan waters is crucial for maximising sustainable fisheries.